PENERAPAN INOVASI MANAJEMEN USAHA DAN STRATEGI PEMASARAN DALAM RANGKA BRANDING PRODUK-PRODUK BATIK CAP MOTIF LAMPUNG PADA UMKM BIQA BATIK - Febrianty, Febrianty; Wuryanti, Lestari; Azdy, Rezania Agramanisti; Sya'ban, Gema Awal; Rahmawati, Nita (LPPM Universitas Bina Bangsa, 2024)
Biqa Batik, a Micro, Small, and Medium Enterprise (MSME) based in Sumberejo, Kemiling District, Bandar Lampung, is this community service partner. It is involved in the craft industry, specifically in stamped batik. Additionally, the MSME and Universitas Malahayati are just 2.8 km apart. In August 2018, Mrs. Lena Agusrini created Biqa Batik. Aspects of marketing strategy and company management are used to categorize the partner's issues. 1) Poor business management; 2) Poor strategic planning; 3) Low operational efficiency; 4) Ineffective marketing strategies; and 5) Limited Use of Marketing Media are the specific problems. The Program Implementation Team has offered the following solutions based on the top issues that need to be resolved: 1. Biqa Batik e-Inventory Implementation and Training; 2. Dyeing Equipment/Place and Training Modification; 3. Biqa Batik e- Catalog Implementation and Training; and 4. Online Marketing Assistance and Training. The proper technology (TTG) that has been used consists of: The following phases of the program are included, and it runs for eight months: Phase I: Situation and Partner Condition Analysis; Phase II: TTG Preparation and Transfer; Phase III: Training and Support for Using website-Based e-Catalog and e- Inventory Applications; and Phase IV: Program Sustainability and Evaluation. The Training and Assistance program uses an approach where the service team goes directly to the field to use the application. Activities include modifying dyeing tubs, providing Business Management Book and tutorial videos for the partner, and providing training and support in business administration via the website-based Biqa Batik e-Inventory and e-Catalog. The activity's outputs include two copyrights (HKI) for computer programs, an ISBN-registered book, publication in the Radar Lampung Newspaper, publication in a Sinta 3 Indexed Journal (ISSN), and a video posted to YouTube. According to the questionnaire results, the partner's degree of empowerment in the business management area has increased by 90%, the marketing element has increased by 87%, and the business management knowledge and abilities have improved by 87%. An 85% increase in the application of the technology supplied to the partner is demonstrated by the use of the relevant technology TTG.